The challenge of simulating the warmth of the mid-Miocene climatic optimum in CESM1 - A. Goldner; N. Herold; M. Huber (Climate of the Past, 2014)
The mid-Miocene climatic optimum (MMCO) is an intriguing climatic period due to its above-modern temperatures in mid-to-high latitudes in the presence of close-to-modern CO 2 concentrations. We use the recently released Community Earth System Model (CESM1.0) with a slab ocean to simulate this warm period, incorporating recent Miocene CO 2 reconstructions of 400 ppm (parts per million). We simulate a global mean annual temperature (MAT) of 18 °C, ~4 °C above the preindustrial value, but 4 °C colder than the global Miocene MAT we calculate from climate proxies. Sensitivity tests reveal that the inclusion of a reduced Antarctic ice sheet, an equatorial Pacific temperature gradient characteristic of a permanent El Niño, increased CO 2 to 560 ppm, and variations in obliquity only marginally improve model–data agreement. All MMCO simulations have an Equator to pole temperature gradient that is at least ~10 °C larger than that reconstructed from proxies. The MMCO simulation most comparable to the proxy records requires a CO 2 concentration of 800 ppm. Our results illustrate that MMCO warmth is not reproducible using the CESM1.0 forced with CO 2 concentrations reconstructed for the Miocene or including various proposed Earth system feedbacks; the remaining discrepancy in the MAT is comparable to that introduced by a CO 2 doubling. The model's tendency to underestimate proxy derived global MAT and overestimate the Equator to pole temperature gradient suggests a major climate problem in the MMCO akin to those in the Eocene. Our results imply that this latest model, as with previous generations of climate models, is either not sensitive enough or additional forcings remain missing that explain half of the anomalous warmth and pronounced polar amplification of the MMCO.